Gut microbiota dynamics in travelers returning from India colonized with extended-spectrum cephalosporin-resistant Enterobacteriaceae: A longitudinal study. Issue 27 (January 2019) - Pires, João; Kraemer, Julia G.; Kuenzli, Esther; Kasraian, Sara; Tinguely, Regula; Hatz, Christoph; Endimiani, Andrea; Hilty, Markus
Abstract: Background: Intestinal colonization by extended-spectrum cephalosporin-resistant Enterobacteriaceae (ESC-R-Ent) has been attributed to travel to high prevalence countries. However, the dynamics of the microbiota changes during ESC-R-Ent colonization and whether there is a particular bacterial composition which is associated with subsequent colonization is unknown. Methods: Forty healthy volunteers living in Switzerland underwent screening before and after a trip to India, and also 3, 6 and 12 months after traveling. Culture-based ESC-R-Ent screening and microbiota analysis based on 16S rRNA amplicon sequencing were performed at all time points. Results: Prevalence of ESC-R-Ent colonization before traveling was 10% (n = 4), whereas it increased to 76% (n = 31) after the trip. Based on bacterial diversity analyses of the gut microbiota, there were few but significant differences for colonized versus non-colonized individuals. However, an alternative, cluster based analysis revealed that individuals remained in the same cluster over time indicating that neither traveling nor ESC-R-Ent colonization significantly influences bacterial composition. Moreover, none of the found microbiota clusters were significantly associated with subsequent risk of ESC-R-Ent colonization. Conclusion: Based on their microbiota patterns, every volunteer was at the same risk of ESC-R-Ent colonization while traveling to India. Therefore, other risk factors for ESC-R-Ent colonization are responsible for this phenomenon.